Pengaruh Penerapan Oral Motor Untuk Anak Speech Delay Usia 2-4 Tahun - Budiarti, Erna; Rahmani, Emma; Yusnita, Erlin; Sumiati, Cucum; Yunaini, Yunaini (Jurnal Pendidikan Indonesia, 2022)
Speech is one aspect of child development that starts from birth. By talking, children can communicate to those around them about themselves, about their condition and about what they want to convey. A child is said to be late in speaking if at the age the ability to process vocals and communicate is not in accordance with the age of the development period or is below the average age of the child. The impact that will be very visible and clearly felt is when communicating with the environment and experiencing difficulties in adaptation and socialization. Oro motor is the movement of the mouth (oral). In newborns this ability is carried out reflexively, then through the learning process an automatic and skilled oromotor will be achieved. Oral motor training is the coordination and movement of hard tissue, soft tissue, vascular system, and control of the nerves in the face and mouth areas that form the function of oral motor. Coordination of these structures is essential for speech, chewing and swallowing with a wide variety of food textures. In general, this paper is to review the results of research that identifies oral motor stimulation increasing the function of orofacial muscles in speech delay children. Method; qualitative descriptive with SSR (Single Subject Research) technique. Literature Review: The oral motor stimulation program includes activities to improve tongue literacy, lip control and chewing power. Oral motor stimulation includes active exercises and passive exercises. Results: The oral motor stimulation program can improve the function of orofacial muscles in children such as pronouncing letters, swallowing food and breathing properly. Language and speech disorders are a type of communication disorder which is indicated by a disturbance in the symbolic process. Language and speech disorders can be caused by disorders of the nervous system or abnormalities in organs related to language and speech processes. Oral motor stimulation can improve the functional ability of the muscles in the mouth area. Good oral motor skills will support the child's speech process.